Avascular Necrosis of the Hip Compromises Gait Balance Control in Female Juveniles With Unilateral Developmental Dysplasia Treated in Toddlerhood - Lee, Wei-Chun; Lee, Pei-An; Chen, Tsan-Yang; Chen, Yu-Ting; Wu, Kuan-Wen; Tsai, Yu-Lin; Wang, Ting-Ming; Lu, Tung-Wu (Frontiers in Bioengineering and Biotechnology, 2022)
Avascular necrosis of the hip (AVN) is one of the most severe complications of surgical reduction when treating developmental dysplasia of the hip (DDH). The current study identified the differences in the balance control during walking in terms of the inclination angle (IA) of the center of pressure (COP) to the center of mass (COM), and the rate of change of IA (RCIA) between female juveniles with and without secondary AVN at the hip who were treated for unilateral DDH during toddlerhood as compared to their healthy peers. When compared to female healthy controls, the non-AVN group showed bilaterally similar compromised balance control with significantly decreased IA (p<0.05) but increased RCIA (p<0.04) in the sagittal plane during single-limb support (SLS) of the unaffected side, and in the frontal plane during terminal double-limb support (DLS) of the affected side. In contrast, the AVN increased between-side differences in the sagittal IA (p=0.01), and sagittal and frontal RCIA during DLS (p<0.04), leading to bilaterally asymmetrical balance control. Secondary AVN significantly reduced IA and RCIA in the sagittal plane (p<0.05), and reduced range of RCIA in the frontal plane during initial DLS (p<0.05). The trend reversed during terminal DLS, indicating a conservative COM-COP control in the sagittal plane and a compromised control in the frontal plane during body weight acceptance, with a compromised COM-COP control in the frontal plane during weight release. The current results suggest that increased between-side differences in the sagittal IA, and sagittal and frontal RCIA during DLS are a sign of AVN secondary to treated unilateral DDH in female juveniles, and should be monitored regularly for early identification of the disease.